Pemikiran Fiqh dan Spirit Transformasi Sosial - Miftahul Huda (Ulumuna, 2009)
In the context of social dynamics and world ideologies contestation that bring social implications, efforts to reconstruct and to revitalize the sharia’s concepts are always be needed. The efforts are aimed at making the sharia remain to be relevant to the needs of. modern societies and to take significant roles in transformation of both individual life and social order. Generally, such a ‘project’ consist of very efforts of reorientation of fiqh visions, reactualizing its methodology, focusing its substance, strengthening the existing social institutions, and developing various new social institutions that are needed as field of small experimentation that will be improved and applied in wider scales in the future. Through the ‘project’ it is hoped that the Islamic law should be simpler but more comprehensive and argumentative. The sharia “face” that up till now seems to be static, conservative, and pro status quo will change to be more alive, innovative, and future-vissioned.